Association between cardiac autonomic modulation and sedentary behavior in breast cancer survivors: a 12-month cohort study - Palma, Mariana R. [UNESP] (2022)
Purpose: This study aimed to analyze the longitudinal influence of sitting time (ST) on cardiac autonomic modulation (CAM) and resting heart rate (RHR) in a 12-month cohort of 67 breast cancer survivors. Methods: CAM was assessed by heart rate variability with heart monitor which also assessed RHR, and ST was self-reported. The relationship between the variables was analyzed by the Pearson correlation and its magnitude by linear regression. Results: At baseline, no associations were found between ST and CAM or RHR. In the delta analyses, a decrease in RMSSD, SD1, and HF(ms2) was associated with sitting time. At 12-month follow-up, there was an increase in the ST and a decrease in RHR. ST was negatively related with CAM (RMSSD, PNN50, and SD1), but no association was observed between ST and RHR. Conclusion: The increase in ST was associated with worsening of CAM after 12-month follow-up. Promoting reduction in ST will be an important strategy against cardiovascular impairment in breast cancer survivors.